Caught off Base: A Note on the Interpretation of Incremental Fit Indices. Issue 6 (2nd November 2022) - van Laar, Saskia; Braeken, Johan
Abstract: This note serves as a reminder that incremental fit indices are a form of standardized effect sizes and hence, all reservations with respect to interpretations of standardized effect sizes also transfer to their interpretation. Such a realization has major implications for the interpretation and use of incremental fit indices, for the theoretical (im)possibility of default universal rules of thumb in their application, and for simulation studies mapping incremental fit indices as if their value is comparable in an absolute sense across any and all conditions. A small but illustrative working example centered around the alleged impact of model type will drive these points home.